Safety Training through gymnastics and sports methods (Fiep Bulletin - online, 2015)
Accidents are assuming an ever-growing importance as technical means of production keep increasing. Their prevention in a real problem in all economically and industrially developed countries. This problem is not a new one: numerous laws bearing on work accidents were passed at the turn of the last century in the midst of the first industrial revolution.